Blended Learning and Sense of Community: A Comparative Analysis with Traditional and Fully Online Graduate Courses - Alfred P. Rovai (Athabasca University Press, 2004)
Blended learning is a hybrid of classroom and online learning that includes some of the conveniences of online courses without the complete loss of face-to-face contact. The present study used a causal-comparative design to examine the relationship of sense of community between traditional classroom, blended, and fully online higher education learning environments. Evidence is provided to suggest that blended courses produce a stronger sense of community among students than either traditional or fully online courses.